The Innate and Adaptive Immune System as Targets for Biologic Therapies in Inflammatory Bowel Disease - Holleran, Grainne (Int J Mol Sci, 2017)
Inflammatory bowel disease (IBD) is an immune-mediated inflammatory condition causing inflammation of gastrointestinal and systemic cells, with an increasing prevalence worldwide. Many factors are known to trigger and maintain inflammation in IBD including the innate and adaptive immune systems, genetics, the gastrointestinal microbiome and several environmental factors. Our knowledge of the involvement of the immune system in the pathophysiology of IBD has advanced rapidly over the last two decades, leading to the development of several immune-targeted treatments with a biological source, known as biologic agents. The initial focus of these agents was directed against the pro-inflammatory cytokine tumor necrosis factor-α (TNF-α) leading to dramatic changes in the disease course for a proportion of patients with IBD. However, more recently, it has been shown that a significant proportion of patients do not respond to anti-TNF-α directed therapies, leading a shift to other inflammatory pathways and targets, including those of both the innate and adaptive immune systems, and targets linking both systems including anti-leukocyte trafficking agents-integrins and adhesion molecules. This review briefly describes the molecular basis of immune based gastrointestinal inflammation in IBD, and then describes how several current and future biologic agents work to manipulate these pathways, and their clinical success to date.